2023
DOI: 10.1186/s10195-023-00707-5
|View full text |Cite
|
Sign up to set email alerts
|

Hormone replacement therapy in women and risk of carpal tunnel syndrome: a systematic review and metaanalysis

Abstract: Background Carpal tunnel syndrome (CTS) is the most common entrapment mononeuropathy. Menopausal status and/or estrogen level may play a role in CTS. The evidence regarding the association between hormone replacement therapy (HRT) in postmenopausal women and CTS is still conflicting. This meta-analysis aimed to investigate the association between carpal tunnel syndrome (CTS) and women using hormone replacement therapy (HRT). Methods A search was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“… 5 , 6 It has been postulated that inflammation of the TCL and tenosynovial tissue within the carpal tunnel can cause CTS. 7 , 8 Toesca et al 3 found high concentrations of estrogen and progesterone receptors in samples of the TCL and synovial tissue from CTS patients, suggesting the carpal tunnel to be a major target for hormonal action. 7 Patients with CAH who are obese and noncompliant will have elevated estrogen in addition to hyperandrogenism secondary to the aromatization of androgens by adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 , 6 It has been postulated that inflammation of the TCL and tenosynovial tissue within the carpal tunnel can cause CTS. 7 , 8 Toesca et al 3 found high concentrations of estrogen and progesterone receptors in samples of the TCL and synovial tissue from CTS patients, suggesting the carpal tunnel to be a major target for hormonal action. 7 Patients with CAH who are obese and noncompliant will have elevated estrogen in addition to hyperandrogenism secondary to the aromatization of androgens by adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of estrogen are also associated with elevated levels of TNF-α, IL-6, and C-reactive protein, which is an acute phase reactant. 7 Maurizio et al 8 , 10 studied the synovial fluid of patients with rheumatoid arthritis and determined that increased estrogen concentrations enhance proinflammatory cytokine secretion and favor the development of immuno-mediated synovitis. Elevated levels of these cytokines can result in cellular proliferation, increased capillary permeability, and edematous changes followed by fibrosis, which can contribute to the development of CTS.…”
Section: Discussionmentioning
confidence: 99%